2017
DOI: 10.1371/journal.pone.0169759
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work after a Stroke in Working Age Persons; A Six-Year Follow Up

Abstract: ObjectivesStroke is one of the most common and resource intensive diseases for society. Stroke in the working age population is increasing in different parts of the world. An incomplete return to work (RTW) after sick leave post stroke entails negative consequences for the affected person and an economical burden for society. The aim of this study was to explore the RTW rate and factors associated with RTW in a six-year follow up post stroke.MethodsData from 174 persons 63 years or younger, with first ever str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 41 publications
7
59
0
1
Order By: Relevance
“…In addition, differences in stroke related factors, which were not registered in this study, might have influenced the results. Many individuals listed as long‐term sick move from rehabilitation to a pension, rather than reaching the goal of RTW (Treger et al., 2007; Westerlind, Persson, & Sunnerhagen, 2017). The tendencies were the same in this study where patients from six of the nine clinics reported a higher percentage of retirement at 1 year post discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences in stroke related factors, which were not registered in this study, might have influenced the results. Many individuals listed as long‐term sick move from rehabilitation to a pension, rather than reaching the goal of RTW (Treger et al., 2007; Westerlind, Persson, & Sunnerhagen, 2017). The tendencies were the same in this study where patients from six of the nine clinics reported a higher percentage of retirement at 1 year post discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The return to work rate within the first year after stroke was reported between 45% to 75%, based on self-reported employment outcomes [23,24]. A more recent Swedish publication, using insurance sickness leave data, reported return to work rate following stroke was 74.7%, at the end of 6-year follow up [25]. Following myocardial infarction (MI), a US study utilizing the data gathered from the VIRGO study reported 84% of patients return to work by 12 months [26].…”
Section: Return To Workmentioning
confidence: 99%
“…Previous studies have provided strong evidence supporting a positive relationship between return to work and reduced or non-impairment (Doucet et al, 2012;Saeki, Ogata, Okubo, Takahashi & Hoshuyama, 1993;Westerlind, Persson & Sunnerhagen, 2017), and several studies have demonstrated difficulty for stroke survivors with sequelae to return to work (Saeki, Ogata, Okubo, Takahashi & Hoshuyama, 1995;Saeki & Toyonaga, 2010). Previous literature about return to work after stroke have suggested correlations with pre-stroke sociodemographic factors including higher education, higher income, and higher socio-economic position (Hannerz, Holbaek Pedersen, Poulsen, Humle & Andersen, 2011;Tanaka, Toyonaga & Hashimoto, 2011;Trygged, Ahacic & K areholt, 2011).…”
Section: Introductionmentioning
confidence: 99%